The Influence of Motivation, Family Factors, and Environment on the Sports Performance of Track and Field Athletes at the Central Java PPLP - Adinda Resta Resta Putri Pratiwi Adinda Resta Putri Pratiwi; Rumini Rumini; Tommy Soenyoto (Journal of Physical Education and Sports, 2026)
Student achievement is influenced by various internal and external factors, among which motivation, family, and environment play significant roles. This study aims to examine the effect of these three factors on student achievement, specifically focusing on athletic performance in track and field athletes of PPLP Central Java. The research employed a quantitative approach using multiple linear regression analysis to assess the relationship between motivation, family support, and learning environment with student achievement. The findings show that motivation has a positive and significant effect on achievement, as indicated by a t-value of 4.942 with Sig. 0.000 < 0.05, meaning that higher motivation leads to better performance. Family support also demonstrates a positive and significant influence, with a t-value of 2.659 and Sig. 0.018 < 0.05, suggesting that stronger family support contributes to improved achievement. Furthermore, the learning environment has a positive and significant effect, with a t-value of 2.287 and Sig. 0.037 < 0.05, indicating that a conducive environment enhances student performance. Overall, the study highlights the importance of motivation, family involvement, and a supportive environment in improving sports achievement among PPLP Central Java athletic athletes, implying that interventions should focus on strengthening these factors to optimize student outcomes.